2013
DOI: 10.1021/jp305935t
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of the Retinal Chromophore in Rhodopsin Mimics

Abstract: Recently, a rhodopsin protein mimic was constructed by combining mutants of the cellular retinoic acid binding protein II (CRABPII) with an all-trans retinal chromophore. Here, we present a combined computational quantum mechanics/molecular mechanics (QM/MM) and experimental ultrafast kinetic study of CRABPII. We employ the QM/MM models to study the absorption (λ(a)max), fluorescence (λ(f)max), and reactivity of a CRABPII triple mutant incorporating the all-trans protonated chromophore (PSB-KLE-CRABPII). We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 127 publications
6
40
0
Order By: Relevance
“…They further emphasized that isolation of the retinal from water is essential for electrostatic tuning of the retinal. In a study of an earlier generation of rhodopsin mimics, Huntress et al . found that limited molecular dynamics sampling is an issue when loosely bound water molecules are near the retinal.…”
Section: Resultsmentioning
confidence: 99%
“…They further emphasized that isolation of the retinal from water is essential for electrostatic tuning of the retinal. In a study of an earlier generation of rhodopsin mimics, Huntress et al . found that limited molecular dynamics sampling is an issue when loosely bound water molecules are near the retinal.…”
Section: Resultsmentioning
confidence: 99%
“…76 Figure 3 reports a pictorial view of optimized geometries as calculated by exploiting a hierarchy of models to account for the environment. The QM portion (the retinal) was treated at the B3LYP/6-31G* level, and the MM portion was held fixed.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
“…Systematic mutagenesis of amino acids close to the chromophore led to absorption spectra ranging from 425 nm up to 644 nm (Sakmar, 2012; Wang et al, 2012). The described artificial spectral tuning through the cellular retinol-binding protein II gave insights into the correlation between electrostatic effects, counter anion, structure of 11- cis -retinal and absorbed wavelength (Huntress et al, 2013). An artificially engineered system such as this experiment demonstrates is the marked ability of 11- cis -retinal to absorb light over a broad spectrum.…”
Section: Molecular Insights Into Color Tuningmentioning
confidence: 99%